Experimental low-temperature heat capacity of one-dimensional xenon adsorbate chains in the grooves of carbon c-SWNT bundles - Bagatskii, M.I.; Manzhelii, V.G.; Sumarokov, V.V.; Barabashko, M.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The experimental studies of the heat capacity of 1D chains of xenon atoms adsorbed in the outer grooves of bundles of closed single-walled carbon nanotubes CXe have been first made at temperature range 2–30 K with the adiabatic calorimeter. The experimental data CXe have been compared with theory [A. Šiber, Phys. Rev. B 66, 235414 (2002)]. The experimental and theoretical heat capacity curves are close below 8 K. Above 8 K the experimental curve CXe (T) exceeds the theoretical one and excess capacity DCXe (T) increases monotonously with temperature. We assume that the DCXe (T) caused mainly by the increase of the distance between the neighboring xenon atoms in the chain with increasing temperature.